Respuesta :

Answer:

b = -9

Step-by-step explanation:

If we have a function with the form:

[tex]f(x)=ax^2+bx+c[/tex]

The axis of symmetry is equal to:

[tex]x = \frac{-b}{2a}[/tex]

So, for the function [tex]f(x)=3x^2+bx+4[/tex], the value of a is 3 and the value of c is 4. It means that its axis of symmetry is equal to:

[tex]x=\frac{-b}{2(3)}=\frac{-b}{6}[/tex]

Solving for b, we get that: [tex]b=-6x[/tex]

Additionally, the axis of symmetry is [tex]x=3/2[/tex], so replacing x by 3/2, we get that b is equal to:

[tex]b=-6(3/2)\\b=-9[/tex]

Answer:

b= -9

Step-by-step explanation:

I just took the quiz and got it right.